Simulação computacional de um circuito de circulação natural utilizando o código RELAP5 - Vinhas, Pedro Andrade Maia (2018)
The use of passive systems such as natural circulation for cooling of nuclear reactor core is an important safety concept. The main advantage of passive sys tems is that. as they just rely on law of physics. they (lo not depend on extern al equipments. RELAP5 code has been widely used in literature for transient and accident simulation that may occur in Light Water Reactors (LVR). Therefore. the main objective of this work is Lo analyze the influence of operational parameters in u atural circulation phenomenon beli avior by rising the computational code RELAP, The circuit implemented in REJA P5 corresponds to the Natural Circulation Circuit (CCX) of the Laboratório de Termohidránlica Experimental of the Instituto de En genharia Nuclear of the Comissão Nacional de Energia Nuclear (LTE/IEN/’CNEN). Several simulations with different combinations of power and cooling water flow rate have been performed. Results show that the nodalization used in such simulations represents the system fairly well and that the code is capable of predicting both single-phase and two-phase flow behavior. However, characteristic circulation ins tabilities have riot been well represented due to the numerical methods used by the computational code.